Long Non-coding RNAs: Regulators of the Activity of Myeloid-Derived Suppressor Cells - Leija Montoya, Gabriela; González Ramírez, Javier; Sandoval Basilio, Jorge; Serafín Higuera, Idanya; Isiordia Espinoza, Mario; González González, Rogelio; Serafín Higuera, Nicolás (Frontiers in Immunology, 2019)
Myeloid-derived suppressor cells (MDSCs) are a heterogeneous cell population with potent immunosuppressive functions. They play major roles in cancer and many of the pathologic conditions associated with inflammation. Long non-coding RNAs (lncRNAs) are untranslated functional RNA molecules. The lncRNAs are involved in the control of a wide variety of cellular processes and are dysregulated in different diseases. They can participate in the modulation of immune function and activity of inflammatory cells, including MDSCs. This mini review focuses on the emerging role of lncRNAs in MDSC activity. We summarize how lncRNAs modulate the generation, recruitment, and immunosuppressive functions of MDSCs and the underlying mechanisms.